FOOD SECURITY DESA TEMBOK KIDUL, KECAMATAN ADIWERNA, KABUPATEN TEGAL PROVINSI JAWA TENGAH - Udin, Ahmad Faqih; Sulaiman, Adiva Muhammad; Lana Zulva, Bagus Mei; Sholikhah, Imroatus; Istiana, Indah; Nur Faizi, Muhammad Ade; Khaitami, Nurman Al (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2023)
Tembok Kidul Village is one of the villages in the Adiwerna sub-district, Kab.  Tegal.  Residents in the village of Lilin Kidul are generally engaged in the industrial sector, where the convection industry is the economic activity of the majority of the residents of the village of Teluk Kidul. The education of the children of the village of Teluk Kidul can be said to be good, for the attention and support of their parents, but there is still a need for a more important role from parents.  parents to support their children's education so they don't drop out of school.  When talking about the level of awareness of the residents of the Kidul Village towards health, it is not optimal.  Such as the lack of health counseling/socialization by the local puskesmas.  Tembok Kidul Village has several assets, one of which is a fishpond which is not far from the village gate.  By analyzing the situation, IBN Tegal students who are carrying out KKN in Tembok Kidul Village have an innovation to process food security programs.  Food Resilience is a condition of fulfilling food for the state down to individuals, which is reflected in the availability of sufficient food, both in quantity and quality, safe, diverse, nutritious, equitable and affordable and does not conflict with the religion, beliefs and culture of society, so that they can  healthy, active and productive life in a sustainable manner.  The aim of this program is to continue the village government program so that later it can be put to good use by the community.  The research method used is community empowerment.  The result of this food resilience is the distribution of fish to collectors who can then use the sales proceeds to raise new seeds